Targeting β2-adrenergic receptor reduces UV-induced cutaneous damage and inflammation in a murine model - Ayaz Shahid; Rita Miwalian; Bradley T. Andresen; Steven Cole; Ying Huang (Journal of Photochemistry and Photobiology)
Preclinical studies demonstrated that the β-adrenergic receptor antagonists (β-blockers) inhibit skin damage and cancer development induced by ultraviolet (UV) radiation, but the mechanism remains unknown. β2-adrenergic receptor (β2-AR) is the predominant adrenergic receptor expressed on skin keratinocytes and immune cells that bind to catecholamines, but its function in UV-induced skin lesions is unknown. Here, the role of β2-AR in UV-induced acute skin damage was investigated using a β2-AR knockout (KO) mouse model. The β2-AR KO mice exhibited attenuated UV-induced skin edema, sunburn, erythema, barrier disruption, apoptosis, and overexpression of IL-6, accompanied by a transient elevation in expression of β1- and β3-ARs. Cytokine array and immunohistochemical analysis of the KO skin revealed reduced UV-induced overexpression of multiple cytokines and chemokines involved in leukocyte infiltration and inflammation. RNA-sequencing analysis confirms that UV triggers a differential transcriptional response between the WT and KO skin. Furthermore, RNA-sequencing identified multiple gene regulatory pathways involved in the KO skin, including reduced activity of the pro-inflammatory transcription factor NF-κB, increased activity of Interferon Response Factors (IRFs) and the glucocorticoid receptor (GR), and reductions in myeloid immune cell/macrophage-related signaling pathways such as CEBP-β and GATA transcription factors. Collectively, these gene regulatory alterations were associated with a substantial reduction in innate immune, inflammatory, and mesenchymal tissue differentiation responses to the UV radiation in the KO skin. These data identify β2-AR as a critical neurobiological pathway involved in UV-induced skin damage and inflammation and support that β2-AR blockade might be useful for preventing UV-related skin lesions and sequelae (e.g., cancers).